2018
DOI: 10.1186/s12866-018-1261-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of human skin allografts and antimicrobial resistance: a skin bank problem

Abstract: BackgroundBacterial contamination remains the major problem in skin banks, even after antimicrobial treatment, and results in high rates of tissue discarding. This study aimed to analyze bacterial contamination in 32 human skin allografts from the skin bank of Dr. Roberto Corrêa Chem from the Hospital Complex Santa Casa de Misericórdia de Porto Alegre. These samples were already discarded due to microbial contamination. The identification of the bacteria isolated from skin allografts was performed by matrix as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The MIC test was susceptible to tetracycline (8.0 mg / litre), vancomycin (4.0 mg / litre), and gentamicin (4.0 mg / litre), but was streptomycin resistant (Adimpong et al, 2012). Moreover, disc diffusion assay was reported for antibiotic resistance profiles in the genus of Bacillus particularly for B. cereus (Gao et al, 2018;Fiedler et al, 2019;Park et al, 2020), in contrast very few was reported for B. licheniformis (Jeong et al, 2017;Meneghetti et al, 2018). Because of the limitation of data which is available about the resistance of B. licheniformis and to provide a guidance value to clinicians encountering possibly B. licheniformis infections; this study was aimed to detect the antibiotic resistance profile of local thermophilic B. licheniformis isolated from soil in Maysan Province, Iraq.…”
Section: Reported Cases Have Suggested That Lichenysinmentioning
confidence: 99%
“…The MIC test was susceptible to tetracycline (8.0 mg / litre), vancomycin (4.0 mg / litre), and gentamicin (4.0 mg / litre), but was streptomycin resistant (Adimpong et al, 2012). Moreover, disc diffusion assay was reported for antibiotic resistance profiles in the genus of Bacillus particularly for B. cereus (Gao et al, 2018;Fiedler et al, 2019;Park et al, 2020), in contrast very few was reported for B. licheniformis (Jeong et al, 2017;Meneghetti et al, 2018). Because of the limitation of data which is available about the resistance of B. licheniformis and to provide a guidance value to clinicians encountering possibly B. licheniformis infections; this study was aimed to detect the antibiotic resistance profile of local thermophilic B. licheniformis isolated from soil in Maysan Province, Iraq.…”
Section: Reported Cases Have Suggested That Lichenysinmentioning
confidence: 99%
“…Table 2 summarizes the susceptibilities, agreement, and kappa statistics for both guidelines. Of the 65 CoNS tested, 10 (15.4%) -CLSI and 14 (21.9%) -BrCAST/EUCAST were resistant to at least three antimicrobial classes and were therefore classified as multidrug resistant (MDR) [9] with a concordance of 93.8% (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…For fast bacterial identification, isolates were plated on Mueller-Hinton agar, and matrix-assisted laser desorption ionizationtime of flight (MALDI-TOF) methodology was performed out in the Microflex LT (Bruker Corporation, USA) platform according to the manufacturer's specifications for direct colony identification. The spectra were analyzed using MALDI Biotyper 4.0 software and standard pattern matching with a default setting in accordance with previously studies [9].…”
Section: Methodsmentioning
confidence: 99%
“…With its long-term storage temperature of 4°C, the low storage and transportation cost is one of the main advantages of the GPA. However, a disadvantage of the method is the observation of occasional contamination by the Bacillus bacteria [7]. Gamma-radiation has also been utilized by surgeons to decrease the contamination rate without harming the function of the skin allograft [8,9].…”
Section: Introductionmentioning
confidence: 99%